From organoids to transplantable artificial kidneys. (4th March 2019) - Naganuma, Hidekazu; Nishinakamura, Ryuichi
Summary: It is difficult to restore kidney function following chronic kidney damage. Although dialysis is currently used to treat patients with chronic kidney disease, it does not cure the disease, while severely restricting the patient's daily and social activities. Kidney transplantation is an alternative and curative therapy, but donor numbers remain limited. However, the generation of kidney organoids from human induced pluripotent stem cells represents an important recent advance in regenerative medicine. Kidney organoids are expected to be used for disease modeling and drug discovery, and may eventually be applicable for transplantation. In this review, we describe the current status of kidney organoids and discuss the hurdles that need to be overcome to generate transplantable artificial kidneys.